2012
DOI: 10.1007/s10865-012-9397-1
|View full text |Cite
|
Sign up to set email alerts
|

Default policies and parents’ consent for school-located HPV vaccination

Abstract: While defaults may encourage some health behaviors, how defaults influence controversial behaviors is not well understood. We examined the effect of two default policies on parents’ consent to have their adolescent sons hypothetically receive HPV vaccine at school. A national sample of 404 parents of adolescent sons participated in an online 3×2 between-subjects factorial experiment. Factors varied the default consent policy (opt-in, opt-out, or neutral) and the number of vaccines sons would receive (HPV vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…9,11,41,63,74 Other studies suggested that policies requiring parental consent prior to HPV vaccine administration to minors may be a barrier to direct communication with adolescents. 107,108 In terms of barriers related to the clinical environment, studies most often identified deficiencies in scheduling as limiting provider communication about HPV vaccination. Providers identified patient reminder/recall as critical to their efforts to recommend HPV vaccination, but many reported that they did not use these systems, and instead relied on patients to initiate scheduling.…”
Section: Visit Typementioning
confidence: 99%
“…9,11,41,63,74 Other studies suggested that policies requiring parental consent prior to HPV vaccine administration to minors may be a barrier to direct communication with adolescents. 107,108 In terms of barriers related to the clinical environment, studies most often identified deficiencies in scheduling as limiting provider communication about HPV vaccination. Providers identified patient reminder/recall as critical to their efforts to recommend HPV vaccination, but many reported that they did not use these systems, and instead relied on patients to initiate scheduling.…”
Section: Visit Typementioning
confidence: 99%
“…[21][22][23][24] The infrequency of adolescent visits to primary care clinics during the ages of 13 to 17 years makes it all the more important to bundle immunizations as a package to ensure initiation and multidose completion.…”
mentioning
confidence: 99%
“…Students in these settings are easier to access, and the school year is long enough to complete vaccination in a multidose series. 24,25 Limitations Given that this research reflects the views and experiences of clinicians and immunization experts who work with underserved ethnic minority and rural populations, it is possible that these findings are relevant to these circumstances and not to conditions of vaccine delivery across the country. Our findings, however, are widely consistent with those reported in the broader literature while offering perspectives that may be uniquely relevant to primary care clinicians and researchers working in similar contexts.…”
mentioning
confidence: 99%
“…7,8 Previous studies have also indicated that parents report greater willingness to consent to having their child receive HPV vaccine in the context of an SLVP that includes multiple adolescent vaccines versus an SLVP that provides HPV vaccine only. 9,10 An SLVP conducted among middle schools in Denver also experienced good uptake of HPV vaccine among those participating in the program; other than the flu vaccine, HPV vaccines were administered most frequently to participants (the denominator of the proportion was all vaccines administered, not unique recipients). 11 The data presented here imply that if participants are already willing to have their child receive vaccines using an SLVP, they will also likely consent for the HPV vaccine through the SLVP.…”
Section: Discussionmentioning
confidence: 99%